Metode Bercakap-cakap: Pengaruhnya terhadap Keterampilan Berbicara Anak Usia 4-5 Tahun - Nuraini Nuraini; Rika Devianti (STAI Auliaurrasyidin Tembilahan, 2021)
Language is the ability to communicate with other people. One of the language skills that can be developed first is speaking skill. Speaking skills need to be optimized because they can affect the next child's life. There are various kinds of problems related to speaking skills including some children who have not been able to communicate the ideas in their minds, express their opinions, and have not dared to speak. In addition, the teaching methods used by teachers have an influence on children's interest in expressing their opinions. This study aims to determine the effect of the conversing method on the speaking skills of children aged 4-5 years. The quantitative approach was carried out using an experimental method of pre-experimental design, one group pretest, and post-test design. Subjects in this study as many as 17 children, data collection techniques using the method of observation and documentation. Furthermore, the data analysis technique used the Wilcoxon Matched Pairs Test formula. The results showed that the method of speaking had an effect on children's speaking skills.